ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INOVASI PRODUK UNUK MENINGKATKAN KINERJA PEMASARAN - Sutopo, Sutopo (Universitas Muhammadiyah Magelang, 2004)
Product innovation conceps are raised in this research as it is viewed as a crucial part to contribute companies success. Researches have shown that many companies face difficulties to increase selling performance. There fore, research on the condept of product innovation is considered as an important research agenda now days. Issues proposed in this research are gap taken from the previous research. Like wise, both variables and indicaors are adapted from research done before. That is, to analyze influence of market orientation tp product innovaion, influence of learning orientation to product innovation, and influence of product innovation to selling performance as well. In this research, the respondents are populations of batik companies in Kabupaten Pekalongan, Central Java. Purposive sampling technique is used to collect datas by giving questionnaries to 100 respondents. Afterwards, the datas are analyzed by using Structural Equation Model (SEM) through AMOS 4.01 program. A model has been developed and 3 hypotheses have been formulated to salve problem in this research. The solution of the problems can be reached through SEM test by using AMOS 4.01 computer program. Result of the research has shown that the inflluence of market orientation to product innovation learning orientation to product innovation, and product innovation to selling performance are positive. Implication on managerial policy, training as well as communications has been proposed as a source of idea for companies in managing their marketing. This research also contributes future research as a base for other research to developed it.